Current fed multipulse rectifier approach for unidirectional HVDC and MVDC applications - Lambert, Gustavo; Vieira Soares, Marcus; Wheeler, Patrick; Lobo Heldwein, Marcelo; Romulo de Novaes, Yales (IEEE, 2018)
Even though multipulse rectifiers are a long established and well-known technology, still their behavior is not fully described in the literature when they are fed by three-phase balanced sinusoidal currents sources. To address the aforementioned gap, this work presents the operation and properties of current-fed multipulse rectifiers. The undertaken aim is achieved by analyzing the examined topology through circuit analysis and then, the theoretical results are validated through comparisons with the simulated waveforms and experimental results. Furthermore, the expected harmonic content and the duality with traditional voltage-fed multipulse rectifiers are presented. In the proposed structure, the transformer voltages present a multipulse waveform, instead of its primary currents as in voltage-fed multipulse rectifiers. This implies on limiting the voltage steps and its derivative which might be beneficial to reduce cost and volume of insulation, particularly for MVDC and HVDC applications. Besides that, by actively controlling the primary currents, a possible copper loss reduction is shown in the transformer windings, differentiating the proposed structure from its voltage controlled counterpart.